2020
DOI: 10.2147/jaa.s258561
|View full text |Cite
|
Sign up to set email alerts
|

<p>Type 2 Inflammatory Biomarker Response After Exercise Challenge Testing</p>

Abstract: Introduction: Exercise-induced bronchoconstriction is due to osmotic stimulus of the airway epithelium and leads to a cascade of biomarker release from several inflammatory cells. Several type 2 (T2) mediators have been linked to exercise-induced bronchoconstriction, but the T2 response per se has not been described during exercise. The aim of this study was therefore to investigate T2 biomarkers in plasma and urine from subjects with asthma and healthy controls before and after an exercise challenge. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition, in the period of immediate preparation for the competition, when the athletes were subjected to the greatest training loads, an increase in IL-10 was shown with no changes in its concentration during the rest period from training. Research results indicate that physical exercise causes a significant increase in IL-13 in non-training people (Tufvesson et al (2020) 43 and Alizadeh et al (2019) 44 ), on the other hand, Zamani et al (2014) 45 showed no significant differences in the concentration of IL-13 in elite wrestlers 24 h after training and in the control group. Observed effect of intense physical exercise on anti-inflammatory cytokines in our study may indicate a high effort tolerability and undisturbed activity of the immune system reacting with rapid activation of anti-inflammatory processes (anti-inflammatory effect of exercise).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the period of immediate preparation for the competition, when the athletes were subjected to the greatest training loads, an increase in IL-10 was shown with no changes in its concentration during the rest period from training. Research results indicate that physical exercise causes a significant increase in IL-13 in non-training people (Tufvesson et al (2020) 43 and Alizadeh et al (2019) 44 ), on the other hand, Zamani et al (2014) 45 showed no significant differences in the concentration of IL-13 in elite wrestlers 24 h after training and in the control group. Observed effect of intense physical exercise on anti-inflammatory cytokines in our study may indicate a high effort tolerability and undisturbed activity of the immune system reacting with rapid activation of anti-inflammatory processes (anti-inflammatory effect of exercise).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the described mechanisms contribute to disrupting the balance between anti-and proinflammatory mediators. Increased physical activity causes systemic endocrine and immune process activation promoting inflammatory process activation [38,41]. It should be noted that most modern authors point to the lack of significant differences between the EIB pathogenesis in adult athletes and high-school teenagers actively involved in sports [9].…”
Section: Peculiarities Of Effort-induced Bronchospasm Pathogenesis In High-school Teenagersmentioning
confidence: 99%
“…Endurance athletes also show increased airway inflammation (Bonsignore et al 2003 ), even though cold exposure per se has limited influence on systemic immune function. An exercise challenge has been shown to increase the levels of the type 2 inflammatory biomarker interleukin-13 in plasma (Tufvesson et al 2020 ). Competitive swimmers, another population with an increased risk of “sports asthma” (Couto et al 2015 ), show signs of increased airway oxidative stress (Morissette et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%